Government Finance Statistics to Strengthen Fiscal Analysis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper seeks Board approval of a phased migration strategy for implementing the GFSM 2001 as the standard for Fund fiscal data. The financial crisis has underscored the need for better and more comparable fiscal data, including on government assets and liabilities. In 2005, the Board endorsed the Government Finance Statistics Manual 2001 (GFSM 2001) and asked staff to propose a migration strategy for the Fund, based on lessons to be drawn from conducting pilot studies. The pilot studies and other tests confirmed that some aspects of the GFSM 2001 methodology (primarily relating to presentation) can be implemented by staff with relatively modest resource needs, while other aspects can proceed meaningfully only after member countries have made sufficient progress in their own fiscal reporting-including in detailed balance sheet breakdowns, and in strengthening underlying accounting systems.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet